Tegal in the Shadow of Colonial Ink: The Narrative Behind the Colonial Press (1900-1942) - Putri, Rona Saharani; Wibowo, Eka Yudha (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
This Study aims to analyze the Dutch colonial press in narrating Tegal between 1900 and 1942. It focuses on how Dutch newspapers shaped and framed realitt for their colonial interests. This study highlights how narrative bias in the colonial press deliberately of colonial government policies, making the narrative of progress and social welfare in Dutch newspapers such as De Locomotief and Bataviaasch Nieuwsblad. This study uses a historical research method divided into four crucial stages: heuristics, verification, interpretation, and historiography. The findings of this study indicate that Tegal was narrated in the news as a vital area for the colonial economy. News about the development and improvement of infrastructure, such as railways and ports, was  framed as an indicator of Tegal’s progress and modernization. Furthermore, the social issue of the malaria epidemic emphasized the rescue efforts of the Dutch East Indies government. Meanwhile, the root of the problem, wich stemmed from their economic policies, was ignored in the narrative. Coverage of community social activities served as a narrative frame for the news to divert attention from the health issues that were occurring in Tegal. In consclusion, in addition to its role as a transmitter of information, the colonial press also served a dual role in fulfillingb the interests of tthe colonial dovernment.